PULMONARY MYCOBACTERIUM TUBERCULOSIS: REVIEW ARTICLE (Academicia Globe: Inderscience Research, 2023)
Pulmonary tuberculosis (PTB) is a contagious diseases caused by bacteria called (Mycobacterium tuberculosis) that usually effect the lungs and it can spread to other parts of the body. TB can cause symptoms such as coughing, chest pain, coughing up blood or phlegm, fever, night sweats, fatigue, and weight loss. TB can be diagnosed with several tests, including a X-ray for chest and a sputum test. Eliminate disease involves taking antibiotics for at least six months. TB can be prevented with a vaccine called the Bacillus Calmette-Guérin (BCG) vaccine and by avoiding contact with people who have active TB. Early diagnosis and medication of Pulmonary tuberculosis are important to prevent the disease.